(untitled) (Chittagong University Journal of Biological Sciences, 2013)
Petroleum ether, carbon tetrachloride, chloroform and ethyl acetate extracts of Plumeria rubra leaves were studied for their antimicrobial activities against eleven human pathogenic bacteria, viz., Shigella dysenteriae, S. sonnei, Salmonella typhi, S. paratyphi, Bacillus subtilis, B. megaterium, B. cereus, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Vibrio cholerae and four human pathogenic fungi, viz., Aspergillus niger, A. ochraceus, A. ustus and Candida albicans using disc diffusion and poisoned food method, respectively. Chloroform and ethyl acetate extract exhibited moderate to good antibacterial and antifungal activity against all the pathogens tested. The ethyl acetate extracts exhibited the largest zone of inhibition (25 mm in diameter with 2000 mg/disc extract) against E. coli. The highest inhibition of fungal radial mycelial growth (62.00% with 100 mg extract/ml medium) was recorded against A. ustus with ethyl acetate extract. The MICs were determined by broth macrodilution technique. The ethyl acetate extract exhibited the lowest MIC (750 mg/ml) against E. coli. However, for fungi the lowest MIC was 500 mg/ml against A. ustus with the same extract. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13409 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):87-94, 2008